Assessment of quality of life and its determinants in type-2 diabetes patients using the WHOQOL-BREF instrument in Bangladesh - Mohammod Feroz Amin; Bishwajit Bhowmik; Rozana Rouf; Monami Islam Khan; Syeda Anika Tasnim; Faria Afsana; Rushda Sharmin; Kazi Nazmul Hossain; Md. Abdullah Saeed Khan; Samiha Mashiat Amin; Md Shek Sady Khan; Md Faruque Pathan; et al. (BMC Endocrine Disorders, 2022)
Abstract Background Diabetes mellitus (DM) is rising at a rapid rate worldwide. As a chronic, incurable metabolic disease, diabetes affects a person’s life in all ways. Studies thus far have focused on the impact of diabetes on the physical and mental health of persons affected by the quality of life (QoL). This study aimed to explore the whole range of QoL deficits using the World Health Organization Quality of Life brief version (WHOQOL-BREF) in type-2 diabetic patients. Methods This cross-sectional study was carried out among individuals aged at or above 15 years with type 2 diabetes (T2DM). Patients with prior mental health illness and unwillingness to give consent were excluded. A pretested structured questionnaire including the 26-item WHOQOL-BREF questionnaire was used for face-to-face interviews. Appropriate ethical measures were ensured. All statistical analyses were carried out using the statistical software STATA (Version 16.1). Graphs were created using R (Version 4.0.0). Results A total of 500 T2 DM patients with a mean age of 55.8 ± 13.2 years (± SD) and a female proportion of 50.8% were included. Overall, 22.2% of participants rated their QoL as poor, and 25% were dissatisfied with their health (as assessed by questions 1 and 2 of the WHOQOL-BREF questionnaire). More than half (54% and 51.2%, respectively) had an average evaluation of their QoL and health. The QoL scores were below average, with mean scores (± SD) for the physical health, psychological, social relationship, and environmental domains of 37.2 ± 20.5, 44.2 ± 21.0, 39.6 ± 23.2, and 41.6 ± 19.5, respectively. Multiple regression analysis revealed that the patient’s level of education and monthly family income were significant positive modifiers and that complications (nephropathy, retinopathy, and peripheral artery disease) were significant negative determinants of the QoL score in different domains. Conclusion This study found the overall quality of life among T2DM patients below average. Health authorities and clinicians should take these findings into account and incorporate necessary measures to ameliorate negative modifiers of the quality of life of sufferers.